1997
DOI: 10.1074/jbc.272.22.14220
|View full text |Cite
|
Sign up to set email alerts
|

Two Oligomeric Forms of Plasma Ficolin Have Differential Lectin Activity

Abstract: Ficolins are plasma proteins with binding activity for carbohydrates, elastin, and corticosteroids. The ficolin polypeptide has a collagen-like domain that presumably brings three subunits together in a triple helical rod, a C-terminal fibrinogen-like domain (fbg) similar to that of tenascin, which presumably has the binding activities, and a small N-terminal domain that we find to be the primary site for forming the ficolin oligomer. By sedimentation equilibrium we determined that the main plasma form, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
44
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 27 publications
(20 reference statements)
4
44
0
Order By: Relevance
“…Trimeric Formation of FD1-The trimerization of ficolins is thought to be mediated by the N-terminal collagen-like region (13,14). However, we found that the recombinant FD1, which lacks the collagen-like region, forms a trimer in solution as judged by a dynamic light scattering experiment in 0.1-1 mg ml Ϫ1 FD1 solution (apparent molecular mass 86.3-88.9 kDa, data not shown).…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…Trimeric Formation of FD1-The trimerization of ficolins is thought to be mediated by the N-terminal collagen-like region (13,14). However, we found that the recombinant FD1, which lacks the collagen-like region, forms a trimer in solution as judged by a dynamic light scattering experiment in 0.1-1 mg ml Ϫ1 FD1 solution (apparent molecular mass 86.3-88.9 kDa, data not shown).…”
Section: Resultsmentioning
confidence: 70%
“…The CRD on MBL, surfactant protein A, and surfactant protein D forms a trimeric structure through a triple ␣-helical coiled-coil at a short neck region between the collagen-like domain and the CRD (10 -12). Ficolins also form trimers (8,13,14), although the mechanism of trimerization is unclear. Both ficolins and collectins form trimer-based multimers that are N-terminally linked by disulfide bonds (15).…”
mentioning
confidence: 99%
“…This structure is also similar to complement protein C1q (21). The primary difference between ficolins and collectins is that the C-terminal globular domain of ficolin is a fibrinogen-like (fbg) domain, whereas that of collectins is a carbohydrate recognition domain (12)(13)(14)26). In addition, collectin family proteins have a short ␣-helical neck region between the collagen and C-terminal domains, whereas ficolins lack this region.…”
mentioning
confidence: 73%
“…Both families of proteins form trimer-based multimers; CL-43 and MBP-C form trimers as the native form, whereas ficolins, conglutinin, MBP-A, and SP-D form tetratrimers (12-mers), and SP-A and C1q form hexatrimers (18-mers) (19 -26, 31, 32). In some cases, larger multimers have been found for ficolin (26), MBP (25), and SP-D (19). Collectin trimers are linked to each other by disulfide bonds in the N-terminal domain (32)(33)(34).…”
mentioning
confidence: 99%
See 1 more Smart Citation